Analysis of a Biomass-fired CCHP System Considering Different Design Configurations. (May 2017) - Caliano, Martina; Bianco, Nicola; Graditi, Giorgio; Mongibello, Luigi
Abstract: This work aims to present the results of an energetic and economic analysis of a biomass fueled CCHP system operating according to different design configurations. The investigated system consists of a biomass-fueled cogeneration unit, an absorption chiller, a thermal energy storage system and a cold one, providing electricity, heat and cooling to an Italian cluster of buildings. For each simulated configuration, the feasible investment cost of the CHP unit is evaluated considering the economic savings obtained with respect to separate generation of electricity, heat and cooling. The best configuration from the economic point of view is indicated, and the incidence of the variation of the absorption chiller and storage systems sizes on the feasible investment cost of the CHP unit is evaluated and discussed as well. Results indicate that the most influencing parameter is represented by the absorption chiller power.